Perilaku Dan Karateristik Peserta Didik Berdasarkan Tujuan Pembelajaran - Hani Hanifah; Susi Susanti; Aris Setiawan Adji (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2020)
This research provides readers with knowledge about the problem and and characteristics of the data discussed in the article. Characteristics and behavior refer to one's character and lifestyle and values that develop regularly so that conduct becomes better and more easily noticed by the student's character is also arguably a specific feature each student has as an individual ora group for consideration and the learning organizing process